Development of a Science Module Based on Problem-Based Learning with an Ecotourism Perspective in Tahura Nuraksa NTB - Huraiza Mahmudah; Yayuk Andayani; Kiki Rizki Maulia; Lailan Khairiawati; Denune Galang Prawira (International Journal of Contextual Science Education, 2025)
Education plays a crucial role in shaping high-quality human resources. The implementation of an independent curriculum requires teachers to foster critical thinking, exploration, and problem-solving skills in students. This study aims to develop a science module based on Problem-Based Learning (PBL) with an ecotourism perspective in Tahura Nuraksa NTB using the 4-D development model (Define, Design, Develop, Disseminate). The developed module enables direct observation of natural phenomena, promotes systematic and analytical thinking, and employs concise, clear language supported by relevant images. The findings indicate that this module enhances student engagement and conceptual understanding, making it an effective learning resource in science education.